Estimating the magnitude of female genital mutilation/cutting in Norway: an extrapolation model - Ziyada, Mai M. (BMC Public Health, 2016)
BACKGROUND: With emphasis on policy implications, the main objective of this study was to estimate the numbers of two main groups affected by FGM/C in Norway: 1) those already subjected to FGM/C and therefore potentially in need for health care and 2) those at risk of FGM/C and consequently the target of preventive and protective measures. Special attention has been paid to type III as it is associated with more severe complications. METHODS: Register data from Statistics Norway (SSB) was combined with population-based survey data on FGM/C in the women/girls’ countries of origin. RESULTS: As of January 1(st) 2013, there were 44,467 first and second-generation female immigrants residing in Norway whose country of origin is one of the 29 countries where FGM/C is well documented. About 40 pct. of these women and girls are estimated to have already been subjected to FGM/C prior to immigration to Norway. Type III is estimated in around 50 pct. of those already subjected to FGM/C. Further, a total of 15,500 girls are identified as potentially at risk, out of which an approximate number of girls ranging between 3000 and 7900 are estimated to be at risk of FGM/C. CONCLUSION: Reliable estimates on FGM/C are important for evidence-based policies. The study findings indicate that about 17,300 women and girls in Norway can be in need of health care, in particular the 9100 who are estimated to have type III. Preventive and protective measures are also needed to protect girls at risk (3000 to 7900) from being subjected to FGM/C. Nevertheless, as there are no appropriate tools at the moment that can single these girls out of all who are potentially at risk, all girls in the potentially at risk group (15,500) should be targeted with preventive measures.